Supply Chain Risk in Pandemic Era - Cakranegara, Pandu Adi (P3KM Politeknik Pertanian Negeri Samarinda, 2022)
Various risks depend on how the risks are classified. Risk can be classified based on predicting the occurrence, or risk can be classified based on systematic or non-systematic. A pandemic like Covid-19 can be put into an unknown systematic risk, meaning that it is an unknown risk that will occur and affect all parts of the economy. One of the things affected is the agricultural sector. This study examines the impact of a pandemic on the supply chain in the agricultural sector, especially in the food commodity sector, where Indonesia still depends on international supply chains. The study method is a descriptive-analytic study using an agricultural supply chain framework. Each part of the supply chain is then analyzed to determine how the framework is generally implemented in Indonesia. The results of this comparison show what policies can be implemented in Indonesia to secure the supply chain for food commodities in Indonesia. This study indicates that the main problem in Indonesia is that there is no guaranteed harvest price for farmers. The consequence is low farmer welfare because farmers cannot produce efficiently.